Polyunsaturated fatty acids levels and initial presentation of somatic symptoms induced by interferon-alpha therapy in patients with chronic hepatitis C viral infection. (28th May 2017) - Chang, Jane Pei-Chen; Lai, Hsueh-Chou; Yang, Hui-Ting; Su, Wen-Pang; Peng, Cheng-Yuan; Gałecki, Piotr; Walczewska, Anna; Pariante, Carmine M.; Su, Kuan-Pin
Abstract : Objectives : Somatic symptoms are common in depressive disorder and are similar to sickness behaviors due to inflammatory activation after cytokine administration. Omega-3 polyunsaturated fatty acids (PUFAs) are natural anti-inflammatory agents and may reduce inflammation-induced behavioral changes. The aim of this study was to investigate the role of PUFAs on the development of somatic symptoms and depression in patients of hepatitis C virus infection (HCV) receiving interferon-alpha therapy (IFN-α) in a prospective manner. Methods : In this 24-week, prospective cohort study, 43 patients with chronic HCV ongoing IFN-α therapy were assessed with the mini-international neuropsychiatric interview for major depressive episodes and neurotoxicity rating scale (NRS) for somatic symptoms. Results : One-third later developed IFN-α-induced depression (depression (DEP) group). As compared to subjects without depression, DEP group had higher NRS scores ( P  < 0.001), lower eicosapentaenoic acid (EPA) levels ( P  = 0.038) at week 2. Somatic symptoms, regardless of painful/non-painful characteristics, had positive association with arachidonic acid ( P  < 0.05), and negative association with EPA ( P  < 0.05). Conclusion : This study implies that early intervention with omega-3 PUFAs might be a promising strategy to prevent depression and somatic symptoms in patients receiving cytokine therapy.